Response of Balangeran (Shorea Balangeran) Plant Growth to the Application of Kiambang (Salvinia molesta) Compost on Peatland - Rahmawati, Reni; Gaman, Sampang; K.F, Eritha; Rosdiana, Rosdiana; A.S., Yosefin; Darung, Untung (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
This study aimed to analyze the effect of Salvinia molesta compost on the growth of Shorea balangeran planted in peatland. The experiment was conducted on peatland in Manen kaleka Village, Pulang Pisau Regency, from July to December 2024. A Randomized Block Design (RBD) was applied with three treatments: P0 (no compost), P1 (200 g kiambang compost), and P2 (400 g kiambang compost), each replicated three times. Observed parameters included plant height increment, stem diameter, number of leaves, and survival rate. Data were analyzed using ANOVA at a 5% significance level, followed by Least Significant Difference (LSD) test for mean comparison. Results showed that Salvinia molesta compost significantly affected Shorea balangeran growth in the field. The P1 treatment (200 g) produced the highest growth with mean height increment of 9.83 ± 1.15 cm and diameter increment of 1.02 ± 0.09 mm compared to the control. The improvement was attributed to increased nutrient availability (N, P, K) and better soil structure due to organic matter addition from decomposed kiambang. Here, Salvinia molesta compost is a promising eco-friendly organic fertilizer for peatland restoration and reforestation efforts.